Is integration of healthy lifestyle promotion into primary care feasible? Discussion and consensus sessions between clinicians and researchers - Arrazola Arantza; Calderon Carlos; Balague Laura; Cortada Josep M; Sanchez Alvaro; Grandes Gonzalo; Vergara Itziar; Millan Eduardo (BMC, 2008)
Abstract Background The adoption of a healthy lifestyle, including physical activity, a healthy diet, moderate alcohol consumption and abstinence from smoking, is associated with a major decrease in the incidence of chronic diseases and mortality. Primary health-care (PHC) services therefore attempt, with rather limited success, to promote such lifestyles in their patients. The objective of the present study is to ascertain the perceptions of clinicians and researchers within the Basque Health System of the factors that hinder or facilitate the integration of healthy lifestyle promotion in routine PHC setting. Methods Formative research based on five consensus meetings held by an expert panel of 12 PHC professionals with clinical and research experience in health promotion, supplied with selected bibliographic material. These meetings were recorded, summarized and the provisional findings were returned to participants in order to improve their validity. Results The Health Belief Model, the Theory of Planned Action, the Social Learning Theory, "stages of change" models and integrative models were considered the most useful by the expert panel. Effective intervention strategies, such as the "5 A's" strategy (assess, advise, agree, assist and arrange) are also available. However, none of these can be directly implemented or continuously maintained under current PHC conditions. These strategies should therefore be redesigned by adjusting the intervention objectives and contents to the operation of primary care centres and, in turn, altering the organisation of the centres where they are to be implemented. Conclusion It is recommended to address optimisation of health promotion in PHC from a research perspective in which PHC professionals, researchers and managers of these services cooperate in designing and evaluating innovative programs. Future strategies should adopt a socio-ecological approach in which the health system plays an essential role but which nevertheless complements other individual, cultural and social factors that condition health. These initiatives require an adequate theoretical and methodological framework for designing and evaluating complex interventions.